Role of Transcerebellar Diameter Measurement with Ultrasonography in Evaluation of Gestational age in Normal and Growth Restricted Fetuses - Singh, Amandeep; Thukral, CL; Singh, Jasmeet; Gupta, Kamlesh; Pahwa, Sangeeta (Asian Journal of Medical Radiological Research, 2019)
Background: To study the usefulness of transcerebellar diameter measurement ultrasonographically for the detection of gestational age in normal and intra uterine growth restricted fetuses and compare the gestation age determined by transcerebellar diameter with that determined by other parameters i.e. biparietal diameter, head circumference, abdominal circumference and femur length. Subjects and Methods: A prospective study with ultrasonographic evaluation of five hundred antenatal patients in gestational age of 14-39 weeks. The transcerebellar diameter was measured and the corresponding gestational age determined. The gestational age was also determined with other parameters such as biparietal diameter, head circumference, abdominal circumference and femur length. Transcerebellar circumference to abdominal circumference ratio was calculated. Results: There is statistically significant relationship between Transcerebellar diameter and gestational age in normal and intra uterine growth retarded pregnancies. Transcerebellar diameter showed good correlation with gestational age (correlation coefficient=0.979) in case of normal pregnancies and( correlation coefficient=0.942 )in cases of intra uterine growth retarded pregnancies Gestational age estimated by transverse cerebellar diameter measurements correlated well with gestational age estimated by biparietal diameter, head circumference, abdominal circumference and femur length. Transcerebellar circumference to abdominal circumference ratio remained fairly constant. Conclusion: Transcerebellar diameter can be used as a independent growth parameter to predict the gestational age in normal and in intrauterine growth retarded pregnancies cases. Transcerebellar diameter to abdominal circumference ratio is fairly constant throughout gestation and thus it is a useful gestational age independent parameter.